Specification for fire hydrant systems equipment Part 4. Boxes for landing valves for dry risers (BSI, 1975)
Fire hydrants, Rising mains, Firefighting equipment, Gate valves, Boxes, Design, Dimensions, Marking, Hydrants, Enclosures